Imaging the Brainstem Raphe in Medication-Overuse Headache: Pathophysiological Insights and Implications for Personalized Care - Annika Mall; Christine Klötzer; Luise Bartsch; Johanna Ruhnau; Sebastian Strauß; Robert Fleischmann (Biomedicines)
Background/Objectives: Medication-overuse headache (MOH) is a disabling condition affecting patients with chronic migraine resulting from excessive use of acute headache medication. It is characterized by both pain modulation and addiction-like mechanisms involving the brainstem raphe, a region critical to serotonergic signaling. This study investigates whether alterations in the brainstem raphe, assessed via transcranial sonography (TCS), are associated with MOH and independent of depressive symptoms, aiming to explore their utility as a biomarker. Methods: This prospective case-control study included 60 migraine patients (15 with MOH) and 7 healthy controls. Comprehensive clinical and psychometric assessments were performed to evaluate headache burden, medication use, and depressive symptoms. TCS was used to assess brainstem raphe echogenicity, with findings analyzed using generalized linear models adjusted for depression. Results: Non-visibility of the brainstem raphe was significantly associated with MOH, with an unadjusted odds ratio (OR) of 6.88 (95% CI: 1.32–36.01, p = 0.02). After adjusting for depressive symptoms, this association remained significant, with an adjusted OR of 1.85 (95% CI: 1.02–3.34, p = 0.041). TCS demonstrated good intraclass correlation, highlighting its reproducibility and ability to detect changes relevant to MOH pathophysiology. Conclusions: Brainstem raphe alterations are associated with MOH and may serve as a potential biomarker for its diagnosis and management. TCS offers a non-invasive, cost-effective tool for identifying MOH-specific mechanisms, which could improve clinical decision-making and support personalized care in chronic headache disorders. Further studies are needed to validate these findings and refine the clinical applications of brainstem-focused diagnostics.